2013
DOI: 10.1177/0093650213510938
|View full text |Cite
|
Sign up to set email alerts
|

Testing Advice Response Theory in Interactions With Friends

Abstract: This study extends and tests advice response theory (ART) by examining message content, message politeness, and advisor characteristics, along with situational and recipient factors as influences on the outcomes of advice. Participants (N = 244) discussed a real, current problem with a friend, completing measures about the advisor, recipient, and situation prior to the interaction, and assessments of advice message qualities and outcomes immediately after. The findings not only support ART but also indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
95
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(110 citation statements)
references
References 39 publications
14
95
0
Order By: Relevance
“…Yet, advice from automation sources such as computers and robots has been largely overlooked by communication scholars. Advice response theory (ART) has emerged and been developed as the main theory of interpersonal advice (Feng & Feng, ; Feng & MacGeorge, ; MacGeorge et al, ; Van Swol, MacGeorge, & Prahl, ). Key aspects of ART include message‐related characteristics (such as the politeness of the message), advisor‐related characteristics (such as expertise), and receiver‐related characteristics (such as emotional state).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, advice from automation sources such as computers and robots has been largely overlooked by communication scholars. Advice response theory (ART) has emerged and been developed as the main theory of interpersonal advice (Feng & Feng, ; Feng & MacGeorge, ; MacGeorge et al, ; Van Swol, MacGeorge, & Prahl, ). Key aspects of ART include message‐related characteristics (such as the politeness of the message), advisor‐related characteristics (such as expertise), and receiver‐related characteristics (such as emotional state).…”
Section: Introductionmentioning
confidence: 99%
“…1.1 | Advice: The message and the advisor The interpersonal process of giving and receiving advice has received considerable attention from communication scholars over the past 20 years (for a review, see Bonaccio & Dalal, 2006;MacGeorge, Guntzviller, Hanasono, & Feng, 2013). Yet, advice from automation sources such as computers and robots has been largely overlooked by communication scholars.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of research has documented that the effects of supportive messages are moderated by a number of factors, including characteristics of the source of support and the situation (see Bodie & Burleson, 2008 for a review). For example, gender moderates the relationship between message content and intent to implement advice, such that message content exerts a stronger influence on intent to implement advice for women than for men (MacGeorge, Guntzviller, Hanasono, & Feng, 2013). In another study, researchers found that HPC messages have a greater effect when support recipients are facing a severe stressor, as opposed to a less serious stressor (Bodie, Burleson, & Jones, 2012).…”
Section: Moderating the Effects Of Supportive Messagesmentioning
confidence: 99%
“…Scholars interested in supportive communication have called for increased research attention on the effects of a support provider on outcomes (Feng & MacGeorge, 2010). The source of a supportive message explains variations in decision-making processes regarding advice (Feng & MacGeorge, 2010;Jungermann & Fisher, 2005), perceptions of support quality and effectiveness (e.g., High & Solomon, 2014;High & Steuber, 2014;MacGeorge et al, 2013), and the extent to which a person copes effectively with a stressor (e.g., High & Solomon, 2014;MacGeorge et al, 2013). The results of this study indicate that different support providers can produce effects prior to an interaction even begins.…”
Section: Theoretical Significance Of Source Effectsmentioning
confidence: 99%
See 1 more Smart Citation